EDUKASI AKTIVITAS ANTIMIKROBA PADA TANAMAN RIMPANG DI WILAYAH KELURAHAN DUREN SAWIT - Eka Sari, Putri; Kartika Falestin, Senny Listi; Rustiana, Nina; Putri, Widya Handayani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Medicinal plants are plants that have properties for preventing and treating disease. Medicinal plants have properties because they contain active compounds resulting from secondary plant metabolism, namely flavonoids, alkaloids, phenols, tannins, saponins, triterpenoids and steroids. Red ginger is a medicinal plant that has been widely studied because it has antibacterial activity. Based on the results of discussions with representatives Duren Sawit Subdistrict, it was found that there had been no education to the public regarding antimicrobial activity in rhizome plants. The aim of this community service is to increase public knowledge regarding the antibacterial potential of native Indonesian rhizome plants. The method used int this activity is providing education through counseling. The results obtained from this activity showed an increase in community knowledge scores before and after being given education about antibacterial rhizome plants.